Manajemen Cadangan Pangan Sebagai Upaya Meningkatkan Ketahanan Pangan Di Kabupaten Ogan Komering Ulu - Witri Miriza; Munajat Munajat; Yetty Oktarina (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN, 2023)
Based on BPS data for 2021, from 13 existing districts in Province South Sumatra, OKU Regency occupiesranking to 12 producers rice. Which means OKU district is not is area barn food. study This aim for analyze howmanagement backup food as effort increase resilience food in OKU District. If compared to between amountproduction rice and amount ideal requirement of rice in OKU district then production rice OKU District yetsufficient For need whole resident OKU District. However need rice in OKU district always sufficient from anotherdistrict. Because although stock rice results production alone Not yet sufficient but access For get rice from regencyother Enough ok. Will but backup food government really needed for countermeasures circumstancesemergency, disaster natural, vulnerable food and overcome turmoil price.